IMPROVEMENT OF SPICE DRINK PACKAGING TO IMPROVE PRODUCT QUALITY AND COMPETITIVENESS AT DANIYAH SUKOHARJO UKM - MATHILDA LESTARI; Maria Puspita Sari; Ainur Komariah (Universitas Sahid Surakarta, 2023)
In this era of the Covid-19 pandemic, many people consume drinks from spices to increase their immune system. The drinks consumed include raw materials from ginger, kencur, turmeric and temulawak, as well as those produced by UKM Daniyah. The production process at SME Daniyah is still traditional. The packaging process is also carried out manually, namely by inserting it into a plastic clip. On this packaging, a label is also given containing product information. But the labeling process only uses photo copies so that the gold processgoes through a long stage. Thefinancial management in SME Daniyah has also not been well documented. So far, financial management has only been recorded in records and manual calculations. This problem encourages our Univet Bantara Sukoharjo Community Service team to facilitate spice shredders and product packaging tools, assist partners in the packaging process to be able to do packaging properly, and assist partners in financial management until partners can carry out financial management with computerization.